The Place Of Listening In The L2 Curriculum: A Review - Floriasti, Tri Wahyuni (Journal of English and Education (JEE), 2013)
In second language research, listening opportunities are often characterized as the linguistics environment – the stage for SLA. This environment, that is, the speakers of the target language and their speech to the L2 learners, provide linguistics input in the form of listening and interaction opportunities embedded in social and pedagogic situations. It has been noted that for a person to learn second language three major conditions are required: (1) a learner who realizes the need to learn the second language and is motivated to do so, (2) Speaker of the target language who know it well enough to provide leaner with access to the spoken language and that support (such as simplification, repletion, and feedback) they need for learning it; and (3) a social setting which bring the leaner in frequent enough and sustain enough contact with target language speakers to make language learning possible. Listening is required in two of these conditions, and is therefore an essential means of language development, a point that is often overlooked in language pedagogy and research. The learner, in order to acquire the language, must come to understand the input and pay attention to the forms in the input. The more students get input from listening, the richer the knowledge they acquire then the more fluent they become. It is educator who need to design and place listening in the right position so that it can bring the leaner in frequent enough and sustains enough contact with target language speakers to make language learning possible.Keywords: Listening, L2 curriculum